2022
DOI: 10.3390/nu14030677
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Running in the D-A-CH Countries? An Epidemiological Approach of 2455 Omnivorous, Vegetarian, and Vegan Recreational Runners—Results from the NURMI Study (Step 1)

Abstract: Accompanied by the growing popularity of distance running, the prevalence of vegan and vegetarian diets in endurance runners has increased across the globe and especially in German-speaking (D-A-CH: Germany, Austria, Switzerland) countries. The present study aimed to investigate and compare the epidemiological characteristics associated with diet types and running behaviors of recreational endurance runners. From a total number of 7422 runners who started to fill in the online survey, 3835 runners completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 58 publications
4
25
1
Order By: Relevance
“…Similar to our study results, a study from Germany also reported a significantly higher proportion female ( p < 0.001) among vegetarians/vegans and were significantly younger than omnivores ( p < 0.001) ( 28 ). These results are in line with most studies that show the same trend for more females being vegetarian than males, regardless of nation/culture ( 6 10 , 21 , 26 ). Moreover, there are studies that showed a strong association between red meat consumption and masculinity ( 29 32 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to our study results, a study from Germany also reported a significantly higher proportion female ( p < 0.001) among vegetarians/vegans and were significantly younger than omnivores ( p < 0.001) ( 28 ). These results are in line with most studies that show the same trend for more females being vegetarian than males, regardless of nation/culture ( 6 10 , 21 , 26 ). Moreover, there are studies that showed a strong association between red meat consumption and masculinity ( 29 32 ).…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that these participants might have poorly planned their diet due to lack of knowledge about a healthy balanced diet. There are studies which have reported that a well-planned vegan/vegetarian diets can provide nutritional requirements to the individuals who are involved in endurance activities ( 14 , 15 , 21 ). The prevalence of underweight among vegan and vegetarian diet participants is high and need to be addressed through awareness programs on healthy balanced diet especially in colleges and universities as vegan and vegetarian diet adoption is higher among the youth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of sex, the health-related dietary patterns found in the vegan runners seem to be associated with a greater health-consciousness of those who follow some kind of vegetarian diet [ 28 ]. Independent of the diet type, however, it has been reported that distance runners rely more on self-designed dietary strategies for training and competition [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, 96% of participants were from Austria, Germany, and Switzerland, suggesting a rather homogenous group in terms of social culture [ 52 ]. Those German-speaking countries are reported to have advanced economies even compared to other western nations, and the results indicate no sex difference in academic qualification, including a predominantly white-caucasian population with high-income levels, high quality of life, and a high life expectancy [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%